2018
DOI: 10.1038/s41598-018-31682-1
|View full text |Cite
|
Sign up to set email alerts
|

TiHo-0906: a new feline mammary cancer cell line with molecular, morphological, and immunocytological characteristics of epithelial to mesenchymal transition

Abstract: Feline mammary carcinomas (FMCs) with anaplastic and malignant spindle cells histologically resemble the human metaplastic breast carcinoma (hMBC), spindle-cell subtype. hMBCs display epithelial-to-mesenchymal transition (EMT) characteristics. Herein we report the establishment and characterization of a cell line (TiHoCMglAdcar0906; TiHo-0906) exhibiting EMT-like properties derived from an FMC with anaplastic and malignant spindle cells. Copy-number variations (CNVs) by next-generation sequencing and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 99 publications
(146 reference statements)
1
15
0
Order By: Relevance
“…Interestingly, the Jak-STAT signalling pathway was the only KEGG pathway enriched with amplified genes in the basal-like TN subtype. Finally, CNGs in F2 64-82.3 Mb (human homologue in HSA 8q) resemble a CNG reported in HBCs 18,41 , canine mammary tumours 82 , and HBC-and FMC-derived cell lines 19,83,84 . This region harbours more than 30 HBC-related genes 19,28,41 , among those MYC, SCRIB, NDRG1, and PTK2 are EMT-related genes frequently amplified in human cancer 21 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, the Jak-STAT signalling pathway was the only KEGG pathway enriched with amplified genes in the basal-like TN subtype. Finally, CNGs in F2 64-82.3 Mb (human homologue in HSA 8q) resemble a CNG reported in HBCs 18,41 , canine mammary tumours 82 , and HBC-and FMC-derived cell lines 19,83,84 . This region harbours more than 30 HBC-related genes 19,28,41 , among those MYC, SCRIB, NDRG1, and PTK2 are EMT-related genes frequently amplified in human cancer 21 .…”
Section: Discussionsupporting
confidence: 58%
“…Among CNGs detected, survival intervals remained negatively influenced by CNGs in B4 1-29 Mb and F2 64-82.3 Mb in the multivariate analysis. The influence of these aberrations on EMT-elicitation in an FMC-derived cell line was described for our group 84 . In this study, these CNGs were associated with poor outcomes and were commonly observed across the population except for the LA subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial to mesenchymal transition is a common pathological process in canine metastatic prostate cancer [90,91]. It is suggested that the analyzed cell lines and respective tumor tissues show features of epithelial to mesenchymal transition, as they express both epithelial (pan-CK, CK7, CK8/18, E-Cad) and mesenchymal (vimentin, Calp) markers concurrently [6,90]. Consequently, epithelial to mesenchymal transition is likely to be advanced in Adcarc1258, as its primary tumor does only express E-Cad as epithelial marker and even this feature gets lost in the cell line.…”
Section: Plos Onementioning
confidence: 99%
“…Consequently, epithelial to mesenchymal transition is likely to be advanced in Adcarc1258, as its primary tumor does only express E-Cad as epithelial marker and even this feature gets lost in the cell line. Adaption processes to culturing conditions or clonal selection of small proportions of tumor cells [6,92,93] may explain the further mesenchymal transition of cell lines Adcarc1508, TCC1509, Adcarc1511.1, Metadcarc1511.2 and Metadcarc1511.3, which is characterized by gains of vimentin and losses of pan-CK expression.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation